Pencatatan Transaksi Setelah Tanggal Pelaporan: Perspektif IPSAS 14 - Muhammad Yunus; Anggi Afnisah; Adam Afiezan; Khairul Amri Hasibuan (PT Syamilah Literasi Islami, 2025)
Events after the reporting date have a significant impact on the reliability of financial statements, both in the private and public sectors. In the public sector, the importance of identifying and classifying these events is crucial because they can influence decision-making, particularly by auditors and other stakeholders. This study aims to analyze the regulation and application of events after the reporting date based on IPSAS 14 and national regulations, namely Minister of Finance Regulation No. 157/PMK.05/2020. The method used is a qualitative descriptive approach through literature study and regulatory analysis. The results of the study indicate that the proper classification of adjusting and non-adjusting events and their adequate disclosure improve the transparency of public sector financial reports. Consistent implementation of these standards also strengthens the accountability of government entities and supports a more reliable audit process.